2021
DOI: 10.21203/rs.3.rs-149170/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Risk Factors for Cholesterol Polyp Formation In The Gallbladder - Closely Related to Lipid Metabolism

Abstract: Objective The purpose of this study was to assess the risk factors for cholesterol polyp formation in the gallbladder. Method This was a multicenter retrospective study based on pathology. From January 2016 to December 2019, patients receiving cholecystectomy and non-polyp participants confirmed by continuous ultrasound follow-ups were reviewed. Patients in the cholesterol polyp group were recruited from three high-volume centers with diagnosis of pathologically confirmed cholesterol polyps larger than 10mm. P… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…This study identi ed decreased HDL signi cantly related to CPs formation, consistent with the survey of Zheng et al, whereas our ndings showed no direct association between CPs and LDL on multivariate analysis despite LDL being associated with CPs on univariate analysis [14]. HDL plays a vital role in accepting cholesterol from cells and promotes reverse cholesterol transportation (RCT), which is essential for maintaining cholesterol metabolism balance in gallbladders [28].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This study identi ed decreased HDL signi cantly related to CPs formation, consistent with the survey of Zheng et al, whereas our ndings showed no direct association between CPs and LDL on multivariate analysis despite LDL being associated with CPs on univariate analysis [14]. HDL plays a vital role in accepting cholesterol from cells and promotes reverse cholesterol transportation (RCT), which is essential for maintaining cholesterol metabolism balance in gallbladders [28].…”
Section: Discussionsupporting
confidence: 89%
“…Our ndings showed that there was no direct association between CPs and obesity. Abnormal liver function is now discovered as a factor correlated to the development of CPs [14]. Although the speci c mechanisms were unknown, the elevation of AST was supposed as a representation of liver damage due to lipid disorder or high metabolism and may indirectly or directly contribute to CPs formation [32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…e law of securities market for many years shows that a large number of companies have deteriorated performance before IPO issuance and during a financial period after IPO listing, which is manifested as a precipitous decline in ROA and ROE [20][21][22]. And this phenomenon is called "performance change" by secondary market participants.…”
Section: Mechanism Explorationmentioning
confidence: 99%